Digitalization of Industrial Processes for Environmental Risk Management at Enterprises - G. E. Ryabik; I. V. Geleta (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет)
The article examines the digitalization of industrial processes as an effective tool for managing environmental risks at enterprises. Emphasis is placed on a comprehensive approach to the use of modern digital technologies – the Internet of Things (IoT), Big Data, analytics, automation, and robotics – aimed at enhancing environmental safety, minimizing the impact of harmful emissions, and optimizing production activities. Special attention is given to the implementation of an intelligent automated system at PJSC “DniproAzot”, which enables the collection, processing, and transmission of CO₂ emissions data in real time. The study analyzes a promising approach to CO₂ emissions utilization through their conversion into carbon-ammonia fertilizers, which combines the reduction of greenhouse gas emissions with economic benefits in the form of valuable agrochemical product output. It is demonstrated that the implementation of digital technologies not only reduces environmental pressure but also contributes to increased productivity, cost reduction, and greater flexibility in enterprise decision-making. The economic feasibility of investing in an intelligent automated system for environmental risk management is substantiated, with calculations provided for potential profit and reduced environmental fees. The role of digitalization in ensuring sustainable development of industrial enterprises amid modern environmental challenges is highlighted. The findings have both practical and theoretical significance for shaping effective environmental policies at the enterprise and national levels.